Solvability of a Three-Point Boundary-Value Problem for a Second-Order Differential Inclusion - Vityuk, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the problem of the existence of solutions of a three-point boundary-value problem for a second order differential inclusion.